2016
DOI: 10.1021/acs.jafc.6b03309
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Antifungal Activity of Juglone (5-Hydroxy-1,4-naphthoquinone) Using a Poly(d,l-lactic-co-glycolic acid) (PLGA) Nanoparticle System

Abstract: This study aimed to synthesize and characterize juglone-entrapped poly(d,l-lactic-co-glycolic acid) (PLGA) nanoparticles and compare the antifungal properties of free juglone with its PLGA nanoparticle formulation for the first time. The juglone-loaded nanoparticles prepared using the oil-in-water (o/w) single-emulsion solvent evaporation method were characterized by the reaction yield (RY), encapsulation efficiency (EE), polydispersity index (PDI), particle size, zeta potential (ZP), FT-IR, and in vitro relea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 50 publications
2
45
0
Order By: Relevance
“…High resolution SEM images of nanoparticles were taken by Field Emission JEOL SEM 7001F under 7–10 kV acceleration voltages (Arasoglu et al . ). Samples were homogeneously coated with 7 nm Au by DC Sputter to prevent the charging effect.…”
Section: Methodsmentioning
confidence: 97%
“…High resolution SEM images of nanoparticles were taken by Field Emission JEOL SEM 7001F under 7–10 kV acceleration voltages (Arasoglu et al . ). Samples were homogeneously coated with 7 nm Au by DC Sputter to prevent the charging effect.…”
Section: Methodsmentioning
confidence: 97%
“…A bioinformatics analysis has shown that bacterial proteins that participate in DNA, RNA and protein synthesis as well as in the tricarboxylic acid cycle are inhibited by juglone [98]. It has also been reported that the antifungal and antibacterial activities of juglone nanoparticles are higher than those of free juglone, indicating that the nanoparticle formulation may be a promising way to enhance the beneficial effects of juglone [100,101].…”
Section: Antimicrobial Activity Of Juglonementioning
confidence: 99%
“…Juglone is studied for its phyto-medicinal applications. This natural compound has anticancer, 7 cytotoxic, and genotoxic, 8,9 antioxidant, 10–12 antiviral, 13 antibacterial, 1416 and antifungal 1722 effects. In traditional medicine, juglone has been used for many years as a treatment for localized, topical fungal infections, such as ringworm.…”
Section: Introductionmentioning
confidence: 99%